Crack characterisation of community structured elements for hydrogel fracture simulation - Teo, Yu Jie (Nanyang Technological University, 2023)
Soft materials, due to their unique properties, often exhibit nonlinear constitutive mechan- ical behaviours, making them a fascinating subject of study. This research project focuses specifically on exploring nonlinear fracture mechanics within the realm of soft materials. Hydrogels, like polyacrylamide hydrogel ("pAAM"), belong to a class of polymers known for their versatility and practical utility in the field of servoelastic control. They find applications in various adaptive bio-micro-electro-mechanical systems, abbreviated as "BioMEMS." It is imperative to understand how these materials fail under fracture. Some of these fracture phenomena include crack blunting, intermittent crack growth, as well as dynamic rupture, or even supershear ruptures. For this project, a fracture model that reflects the observed real-world crack shape based on shape comparisons with experimental data, as well as the stress-strain characteristics, was developed by extending a random multiplex mesoscopic network topology to derive material parameters associated with a macroscopic phase field finite element model. New techniques were employed to construct this model. This includes utilizing network efficiency and distance measures to extend the Lake-Thomas estimation of fracture energy, as well as coarse-graining the network to derive representative material parameters for a finite element model. This paper primarily details attempts to compare the crack growth in simulations to experimental meandering cracks using metrics from geometry, such as sinuosity, curvature, and circular statistics of the gradient of the crack. These attempts were successful in validating the shape of the cracks where the finite element simulation were significantly more accurate (within 5% accuracy) for all relevant metrics to other potential test functions that are similar but not the same as the crack.